2021
DOI: 10.1021/acsnano.1c08691
|View full text |Cite
|
Sign up to set email alerts
|

Nonintrusion Monitoring of Droplet Motion State via Liquid–Solid Contact Electrification

Abstract: Droplet motion state monitoring is important in microfluidic applications, such as biomedicine, drug delivery, and metal ion extraction. Here, a nonintrusion monitoring method of droplet motion state via liquid–solid contact electrification is proposed, and a triboelectric droplet motion state sensor (TDMSS) is fabricated. Droplet counting and droplet size monitoring can be realized by signal processing and information extracting of the voltage pulse. The experimental results show that the number of droplets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…38 Song et al produced a triboelectric droplet motion state sensor (TDMSS), which could realize droplet counting and droplet size monitoring. 39 These research results show that the sensing method based on a liquid−solid contact TENG is feasible and stable.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…38 Song et al produced a triboelectric droplet motion state sensor (TDMSS), which could realize droplet counting and droplet size monitoring. 39 These research results show that the sensing method based on a liquid−solid contact TENG is feasible and stable.…”
Section: Introductionmentioning
confidence: 73%
“…Zhang et al constructed an RDE-TENG that obtained the energy of raindrops, which could monitor the temperature and humidity in the greenhouse . Song et al produced a triboelectric droplet motion state sensor (TDMSS), which could realize droplet counting and droplet size monitoring . These research results show that the sensing method based on a liquid–solid contact TENG is feasible and stable.…”
Section: Introductionmentioning
confidence: 99%
“…The detection accuracy can reach 100% when the time interval between two continuous bubbles is not less than 0.3 s. Song et al also fabricated a triboelectric droplet motion state sensor (TDMSS) based on the gas-liquid two-phase flow. [100] It is found that the number of output voltage pulses has a linear relationship with the liquid input flow rate. The TDMSS can stably achieve droplet counting.…”
Section: Gas-liquid Two-phase Flowmentioning
confidence: 99%
“…also fabricated a triboelectric droplet motion state sensor (TDMSS) based on the gas–liquid two‐phase flow. [ 100 ] It is found that the number of output voltage pulses has a linear relationship with the liquid input flow rate. The TDMSS can stably achieve droplet counting.…”
Section: Triboelectric Fluid Sensorsmentioning
confidence: 99%
“…However, due to the need for direct contact with the liquid, they may have drawbacks of sample contamination and analytical complexity. 16 In contrast, non-invasive liquid probes possess unique advantages in assessing liquid characteristics by observing how the liquid interacts with wireless signals 17,18 or optoelectronic detection. Wireless signal-based liquid probes such as radio frequency identification 19 are limited by the need for additional signal emissions, restricting their widespread applications.…”
Section: Introductionmentioning
confidence: 99%